Analisis Kandungan Mikroba, Formalin, dan Timbal (Pb) pada Tahu Sumedang yang Dijual Di Daerah Macet Cicurug, Ciawi, dan Cisarua Jawa Barat - Rosy Hutami; M Fakih Kurniawan; Henna Khoerunnisa (JURNAL AGROINDUSTRI HALAL, 2020)
Sumedang tofu is one of favorite foods for Indonesian society. But many sellers or producers are not aware to the food safety of sumedang tofu. The aims of this study were to analyze the microbial, formalin, and lead (Pb) contents in ready-to-eat sumedang tofu which were sold in traffic jams area in Cicurug, Ciawi, and Cisarua. The analysis were carried out by Total Plate Count (TPC) testing for microbial analysis, potassium permanganate reaction (KMnO4) testing for formaldehyde analysis, and atomic absorption spectrophotometry (AAS) method for lead content analysis in the samples. The results obtained for the microbial analysis were sumedang tofu that were sold in the traffic jam areas of Cicurug, Ciawi, and Cisarua contained contaminant above the treshold (1.4 x 105 colonies / gram to 2.2 x 105 colonies / gram of microbes). All of the samples of sumedang tofu were positive containing formaldehyde. Otherwise, there were no lead (Pb) content in all samples regarding to AAS analysis. This study concluded that the ready-to-eat sumedang tofu those were sold in traffic jam area in the Cicurug, Ciawi, and Cisarua were not suitable for consumption because it contained exceed microbial contamination and formalin which are harmful for human health.Keywords : formalin, microbes, sumedang tofu, lead, traffic jam